EFL STUDENTS’ VOICES ON LEARNER AUTONOMY AT A UNIVERSITY IN THE MEKONG DELTA - Anh, Le Thanh Nguyet (VNU Journal of Foreign Studies, 2018)
The present study aimed to investigate students’ learner autonomy (LA) at tertiary education in Vietnam. The study participants were 60 English as a Foreign Language (EFL) students from a single rural university, South Vietnam. Narrative interview was used to collect the required data. The findings disclosed that most of them had positive views of LA as well as its role at higher education. Yet, in LA practices, they gained achievements of diﬀerent degrees and related problems were found. Thereby, it implied that since LA was a long process, students should patiently keep on cultivating it by virtue of both their own sufcient ongoing eﬀorts and instructor’s supports in need.